ABCD REQUIREMENTS OF LESSON OBJECTIVES MADE BY THE ENGLISH DEPARTMENT STUDENTS OF UNLAM FOR PRAKTEK PENGENALAN LAPANGAN (PPL) I COURSE - Elvina Arapah (FKIP ULM, 2016)
Abstract: Writing a lesson objective is still a challenging task for the English Department students of Lambung Mangkurat University when they do their micro teaching practice in Praktek Pengenalan Lapangan (PPL) I Course. The formulated lesson objectives have to include the ABCD elements -Audience/Actor, Behavior, Condition, Degree- which require distinct characteristics for each. The study examines the lesson objectives of the lesson plans made by the English Department students of Lambung Mangkurat University for PPL I Course in the Academic Year of 2010/2011. There are 91 lesson plans were collected, and there are 91 lesson objectives investigated. The findings discuss the formulation of ABCD requirements in the lesson objectives. It is recommended that the students’ English proficiency must be enhanced because the formulation of a good lesson objective is closely related with the ability to produce grammatically correct sentence. Key words: Lesson Objectives, Audience, Behavior, Condition, Degree Abstrak: Menulis tujuan pembelajaran masih merupakan tugas yang menantang bagi mahasiswa Program Studi Pendidikan Bahasa Inggris, Universitas Lambung Mangkurat ketika mereka melakukan praktek pembelajaran mikro dalam Mata Kuliah Praktek Pengenalan Lapangan (PPL) I. Tujuan pembelajaran yang dirumuskan harus mencakup unsur-unsur ABCD -Audiens/Aktor, Perilaku, Kondisi, Taraf- yang membutuhkan karakteristik berbeda untuk masing-masing unsur. Studi ini meneliti tujuan pembelajaran dari Rencana Pembelajaran (RP) yang dibuat oleh mahasiswa Program Studi Pendidikan Bahasa Inggris, Universitas Lambung Mangkurat untuk Mata Kuliah PPL I Course di Tahun Akademik 2010/2011. Ada 91 rencana pembelajaran dikumpulkan, dan ada 91 tujuan pembelajaran yang diteliti. Temuan membahas perumusan dari syarat ABCD di tujuan pembelajaran. Disarankan bahwa kemampuan bahasa Inggris siswa harus ditingkatkan karena perumusan tujuan pembelajaran yang baik terkait erat dengan kemampuan untuk menghasilkan kalimat dengan tata bahasa yang benar. Kata kunci: Tujuan Pembelajaran, Audiens/Aktor, Perilaku, Kondisi, Taraf